The Trickery of the Fallen Angels and the Demonic Mimesis of the Divine: Aetiology, Demonology, and Polemics in the Writings of Justin Martyr - Reed, Annette Yoshiko (Journal of early Christian studies, 2004)
This article examines Justin's appeal to Gen 6.1–4 to explain the origins of pagan worship. In an innovative twist on earlier Jewish traditions, he proposes that the progeny of the fallen angels became demons who masquerade as deities and trick pagans into persecuting Christians. Justin's demonization of Greco-Roman religion contrasts both with his approach to Hellenistic philosophy and with his appeal to the disobedience of Adam and Eve to explain Jewish wickedness. Analysis of his demonology thus sheds light on his strategies for explaining similarities between Christianity and Greco-Roman culture as well as his understanding of the condition of the unsaved pagan as distinct from both Christians and Jews.